The Reilly's Integral Formula on Semi-Riemannian Manifolds with Nondegenerate Boundary - Ergut, Mahmut; Kulahci, Mihriban (Soc Paranaense Matematica, 2013)
In this paper, we obtained the Reilly's integral Formula on semi Riemannian manifolds with nondegenerate boundary.
Keywords: Semi-Riemannian manifold; Nondegenerate boundary; Reilly's formula